Carotid intima-media thickness and cardiac functions in children with neurofibromatosis type 1 - Arslan, Alev (Journal of Surgery and Medicine, 2019)
Aim: Neurofibromatosis type 1 is a multisystem disorder, affecting primarily the skin, nervous and musculoskeletal systems. Various cardiovascular abnormalities, ranging from congenital heart disease to vasculopathy and hypertension are main clinical features of cardiovascular involvement. The aim of this study was to evaluate cardiac functions and carotid intima-media thickness by conventional and tissue Doppler echocardiography in terms of vasculopathy and cardiac involvement in children with neurofibromatosis type 1. Methods: A cross-sectional study is designed with 36 Neurofibromatosis patients (20 boy and 16 girl) as study group, with a mean age of 9.7(3.5) years with 36 healthy controls (18 males and 18 females) with a mean age of 10.3(2.2) years. Instant blood pressures were measured. Conventional and tissue Doppler echocardiography were performed. Carotid intima-media thickness, left ventricular ejection fraction and left ventricular fractional shortening were measured with M mode. Mitral early (E), late (A) flow velocities were measured by pulsed-wave Doppler, mitral early (E), late (A) flow velocities ratio was calculated. Tissue Doppler echocardiography was performed from the lateral annular junction of mitral valve and left ventricular myocardial performance index (Tei) index was calculated. Early diastolic flow (E’) velocity was measured with tissue Doppler echocardiography. Results: Left ventricular systolic functions were normal in both groups. Mitral early flow velocities were lower (P<0.001) in the study group. Also Mitral early / late velocities ratio was significantly lower (P=0.004) and mitral early flow velocity/ tissue Doppler early diastolic flow velocity ratio was higher (P=0.045) in the study group. The left ventricular Tei index was calculated as 0.42 (0.1) in the study group and 0.39 (0.1) in the healthy controls (P=0.03). The mean of carotid intima-media thickness was 0.46 (0.01) in the study group and 0.44 (0.01) in the control group (P=0.002). Systolic blood pressures were higher in the study group (P=0.04). Conclusion: Tei index and diastolic flow velocities in mitral valve support the left ventricle diastolic dysfunction in children with neurofibromatosis type 1. Carotid intima-media thickness suggests vasculopathy and early effects of hypertension due to neurofibromatosis type 1.